Long non-coding RNA HOTAIR promotes exosome secretion by regulating RAB35 and SNAP23 in hepatocellular carcinoma - Yang, Liang (Mol Cancer, 2019)
BACKGROUND: Emerging evidence indicates that tumor cells release a large amount of exosomes loaded with cargos during tumorigenesis. Exosome secretion is a multi-step process regulated by certain related molecules. Long non-coding RNAs (lncRNAs) play an important role in hepatocellular carcinoma (HCC) progression. However, the role of lncRNA HOTAIR in regulating exosome secretion in HCC cells remains unclear. METHODS: We analyzed the relationship between HOTAIR expression and exosome secretion-related genes using gene set enrichment analysis (GSEA). Nanoparticle tracking analysis was performed to validate the effect of HOTAIR on exosome secretion. The transport of multivesicular bodies (MVBs) after overexpression of HOTAIR was detected by transmission electron microscopy and confocal microscopy analysis of cluster determinant 63 (CD63) with synaptosome associated protein 23 (SNAP23). The mechanism of HOTAIR’s regulation of Ras-related protein Rab-35 (RAB35), vesicle associated membrane protein 3 (VAMP3), and SNAP23 was assessed using confocal co-localization analysis, phosphorylation assays, and rescue experiments. RESULTS: We found an enrichment of exosome secretion-related genes in the HOTAIR high expression group. HOTAIR promoted the release of exosomes by inducing MVB transport to the plasma membrane. HOTAIR regulated RAB35 expression and localization, which controlled the docking process. Moreover, HOTAIR facilitated the final step of fusion by influencing VAMP3 and SNAP23 colocalization. In addition, we validated that HOTAIR induced the phosphorylation of SNAP23 via mammalian target of rapamycin (mTOR) signaling. CONCLUSION: Our study demonstrated a novel function of lncRNA HOTAIR in promoting exosome secretion from HCC cells and provided a new understanding of lncRNAs in tumor cell biology. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12943-019-0990-6) contains supplementary material, which is available to authorized users.